Anti-Contractile and Anti-Inflammatory Effects of Diacerein on Isolated Mouse Airways Smooth Muscle and Mouse Asthma Model - Shi, Shunbo; Xue, Lu; Han, Shuhui; Qiu, Haiting; Peng, Yongbo; Zhao, Ping; Liu, Qing-Hua; Shen, Jinhua (Frontiers in Pharmacology, 2020)
Characterized by abnormal smooth muscle contractility and airway inflammation, asthma is one of the most common airway diseases worldwide. Diacerein is a well-known anti-inflammatory drug, widely used in osteoarthritis. In current study, the innovative usage of diacerein in anti-contractile and anti-inflammatory treatment of asthma was studied. In vitro experiments including tension measurement and patch-clamp technique and in vivo experiments including establishment of mice model and measurement of respiratory resistance were applied to explore the role of diacerein in asthma. It turned out that agonist-precontracted mouse airway smooth muscle could be relaxed by diacerein via intracellular and extracellular calcium mobilization which was mediated by switched voltage-dependent L-type Ca2+ channels, non-selective cation channels, large-conductance Ca2+-activated K+ channel and Na+/Ca2+ exchangers. Furthermore, diacerein could relieve bronchospasm and control airway inflammation in asthmatic mice via reduction of several inflammatory factors. Our studies elucidated the potential therapeutic property of diacerein in asthma treatment and the possible underlying mechanism. It also confirmed that new uses for already-approved drugs could be an important form of innovation.